PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PENERAPAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN PENGAWASAN KEUANGAN SEBAGAI VARIABEL MODERASI PADA KOPERASI DI WILAYAH KABUPATEN SLEMAN - Susliyanti, Eni Dwi; Handayani, Ch.Dini Ika (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
The quality of financial statements serves as a benchmark for an organization’s success in presenting information that is relevant, reliable, understandable, and comparable for users. High-quality financial statements not only reflect the organization’s performance but also form the basis for managerial decision-making and strategic policy formulation. Several factors may influence the quality of financial statements. This study examines the effect of human resource quality and the implementation of accounting information systems on the quality of financial statements, with financial supervision as a moderating variable in cooperatives located in Sleman Regency. The results show that: (1) the quality of human resources (HR) has a positive and significant effect on the quality of financial statements; (2) the implementation of accounting information systems (AIS) has a significant but negative effect on the quality of financial statements; (3) financial supervision moderates the effect of HR quality on the quality of financial statements in a negative direction; (4) financial supervision moderates the effect of AIS implementation on the quality of financial statements in a positive direction. This indicates that financial supervision plays an important role in ensuring that AIS implementation is carried out according to procedures, thereby improving the quality of financial statements; (5) the coefficient of determination (R²) is 0.636, meaning that 63.6% of the quality of financial statements is influenced by HR quality, AIS implementation, and their interaction with financial supervision, while the remaining 36.4% is influenced by other factors not examined in this study. Keywords: human resource quality, accounting information system implementation, financial supervision, cooperatives, financial statement quality.